Genome diversity of Leishmania aethiopica - Hadermann, Amber; Heeren, Senne; Maes, Ilse; Dujardin, Jean-Claude; Domagalska, Malgorzata Anna; Van den Broeck, Frederik (Frontiers in Cellular and Infection Microbiology, 2023)
Leishmania aethiopica is a zoonotic Old World parasite transmitted by Phlebotomine sand flies and causing cutaneous leishmaniasis in Ethiopia and Kenya. Despite a range of clinical manifestations and a high prevalence of treatment failure, L. aethiopica is one of the most neglected species of the Leishmania genus in terms of scientific attention. Here, we explored the genome diversity of L. aethiopica by analyzing the genomes of twenty isolates from Ethiopia. Phylogenomic analyses identified two strains as interspecific hybrids involving L. aethiopica as one parent and L. donovani and L. tropica respectively as the other parent. High levels of genome-wide heterozygosity suggest that these two hybrids are equivalent to F1 progeny that propagated mitotically since the initial hybridization event. Analyses of allelic read depths further revealed that the L. aethiopica - L. tropica hybrid was diploid and the L. aethiopica - L. donovani hybrid was triploid, as has been described for other interspecific Leishmania hybrids. When focusing on L. aethiopica, we show that this species is genetically highly diverse and consists of both asexually evolving strains and groups of recombining parasites. A remarkable observation is that some L. aethiopica strains showed an extensive loss of heterozygosity across large regions of the nuclear genome, which likely arose from gene conversion/mitotic recombination. Hence, our prospection of L. aethiopica genomics revealed new insights into the genomic consequences of both meiotic and mitotic recombination in Leishmania.